Innovation Packages and Scaling Readiness workshop: Point of Cow - Moodley, Arshnee; Mhone, Amos L.; Muloi, Dishon M.; Ibayi, Eugine; Hung Nguyen-Viet; Jasada, Ijudai; Buono, Nicoletta (International Livestock Research Institute, 2024)
This report delves into the insights gained from an innovation packages and scaling readiness workshop, identifying user needs and challenges, and ultimately designing an innovation package to propel the Point of Cow diagnostic test kit to successful scaling to ensure that by the end of 2024, ILRI and its partners will collaborate with a local diagnostic company, national and county government bodies, and regulatory authorities to roll out the Point of Cow technology. We intend to engage 200 animal health service practitioners and 50,000 dairy farmers in the central and western regions of Kenya, ensuring that 80% are smallholders. The goal is to boost farm income and reduce antibiotic use by 20%.